Kontribusi Pendidikan IPS Terhadap Pembentukan Karakter Sosial Peserta Didik di Sekolah Dasar - Siprianus See (Ekspektasi: Jurnal Pendidikan Ekonomi, 2022)
Social Science Education (IPS) in principle provides students with knowledge and experience about social life.  This is contained in the purpose and dimensions of social studies education which as a whole touches all aspects of students' lives.  Through social studies education, students from an early age at elementary school age can be helped in shaping their social character. Social studies education in elementary schools teaches the concepts and realities of social life that are essential to shape students into citizens who are able to live and practice social character which is realized through social skills in living with others. Social Studies is one of the media that is able to make an effective contribution to students to be able to have mental, personality and social skills based on morals, all of which are ideals of the expected character values of students. The ideal social character of students as aspired by this nation is students who are devoted to God Almighty, knowledgeable, ready to work together, work together and are willing to sacrifice for fellow citizens. The close relationship between social studies learning and the formation of the social character of students requires teachers, especially elementary school teachers, to be able to succeed in social studies learning more effectively and efficiently.